2019
DOI: 10.1128/jb.00622-18
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Starvation Induces Persister Cell Formation in Escherichia coli

Abstract: To cope with fluctuations in their environment, bacteria have evolved multiple adaptive stress responses. One such response is the nitrogen regulation stress response, which allows bacteria, such as Escherichia coli, to cope with and overcome conditions of nitrogen limitation. This response is directed by the two-component system NtrBC, where NtrC acts as the major transcriptional regulator to activate the expression of genes to mount the response. Recently, my colleagues and I showed that NtrC directly regula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 30 publications
6
28
0
Order By: Relevance
“…5A-C). Recently, RelA-dependent antibiotic tolerance was also observed during nitrogen starvation (Brown, 2019). Interestingly, the observation that the antibiotic tolerance induced by FA inhibitors can be completely reversed by supplementing lysine shows therapeutic potential of our study ( Fig.…”
Section: Discussionsupporting
confidence: 71%
“…5A-C). Recently, RelA-dependent antibiotic tolerance was also observed during nitrogen starvation (Brown, 2019). Interestingly, the observation that the antibiotic tolerance induced by FA inhibitors can be completely reversed by supplementing lysine shows therapeutic potential of our study ( Fig.…”
Section: Discussionsupporting
confidence: 71%
“…We have shown that a one-hour starvation pulse prior to the addition of the antibiotic affects long-term survival. This finding is consistent with a previous study of a temporal nitrogen downshift prior to antibiotics treatment, which was shown to elevate the persister level at 24 hours in a relA dependent manner [29]. Our study demonstrated that the memory can be remarkably long-lasting, as one-hour carbon starvation gave an increase in survival for at least 4 days in the wildtype strain grown in glucose medium.…”
Section: Discussionsupporting
confidence: 93%
“…Our transcriptome analysis identified that crucial transcriptional regulators were massively downregulated in Δdam (Supplementary Table 2), these regulators are known to be involved in persister formation with the actication of stress response, including LexA 44 NtrB 45 , Fis 46 , Fnr, Lrp 47 , SoxS 48 , ArcA 47 49 , which may be responsible for the defect in persister formation in the Δdam mutant or survival in various stresses as shown in this study. It also revealed that demethylation in the Δdam mutant impaired persister formation by affecting extensive gene expression, such as upregulating genes involved in flagellar synthesis and assembly and galactose metabolism, propanoate metabolism and downregulating genes involved in different types of fimbrial biosynthesis, pilus synthesis, metabolism (carbon and nitrogen source), sugar phosphotransferase systems (PTS) and secretion-related pathways.…”
Section: Discussionsupporting
confidence: 51%